Biomechanical determinants of shuttlecock speed in the forehand jumping smash by elite male Malaysian badminton players / Yuvaraj Ramasamy - Yuvaraj, Ramasamy (2021)
Badminton is the fastest racket sport in the world with smash speeds reaching over 111 m/s (400 kph). This study examined the forehand jump smash in badminton using synchronised force plates and full-body motion capture to quantify contributions to shuttlecock speed through correlations. Nineteen elite male Malaysian badminton players were recorded performing forehand jump smashes with the fastest, most accurate jump smash from each player analysed. The fastest smash by each participant was on average 97 m/s with a peak of 105 m/s. A correlational analysis revealed that a faster smash speed was characterised by a more internally rotated shoulder, a less elevated shoulder, and less extended elbow at contact. The positioning of the arm at contact appears to be critical in developing greater shuttlecock smash speeds. Vertical ground reaction force and rate of force development were not correlated with shuttlecock speed, and further investigation is required as to their importance for performance of the jump smash e.g. greater jump height and shuttle angle. It is recommended that players/coaches focus on not over-extending the elbow or excessively elevating the upper arm at contact when trying to maximise smash speed.